Metathesis in Najdi Arabic: An Optimality Theoretic Analysis - Reema H. Al Toreegi; Metab M. Alhoody (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Metathesis is a phonological phenomenon involving the reordering of segments within words. Despite its presence in Arabic dialects, it has received limited scholarly attention, particularly within Saudi varieties. Furthermore, this phenomenon has not been systematically investigated in these varieties within the framework of Optimality Theory (OT). The current study presents a systematic analysis of consonant, long vowels, and VVC metathesis in Najdi Arabic (NA), a dialect spoken in central Saudi Arabia within the OT framework. It examines the extent to which phonetic, phonological, and morphological factors influence metathesis in NA and demonstrates how OT effectively accounts for the reordered patterns. Data were gathered from publicly available social media posts by NA speakers and from my collection of metathesized words, compiled as a native NA speaker from other native NA speakers. The analysis reveals that metathesis in NA is highly motivated by phonological conditions, particularly the Syllable Contact Law and the Sonority Sequencing Principle, as well as phonetic factors, such as the tendency to pronounce articulatory effortful sounds earlier in the sequence. The primary constraints identified are MAX-IO, SCL-STOP, *LATE-STRONG, SSP, and LINEARITY. Besides, it occurs in trilateral roots in verbs, while it happens in trilateral and quartiles in nouns. The findings show that metathesis in NA is shaped by the interaction among variant linguistic domains rather than by a single actor. The study concludes by proposing future experimental investigations into native NA speakers’ perception and production of different types of metathesis in NA.